Clinical and imaging associations for non-ketotic hyperglycemic chorea: a case-control study - Liang, Zhuo-Yuan; Lu, Zhi-Hao; Qu, Jian-Feng; Chen, Yang-Kun (Frontiers in Endocrinology, 2023)
Background The non-ketotic hyperglycemic chorea (NKHC) was a rare complication for patients with diabetes mellitus, but not been well studied. In the present research, we aimed to investigate the clinical and imaging characteristics of NKHC and explore the potential association. Methods We performed a case-control study with patients diagnosed as NKHC. The patients with group of NKHC were retrospectively recruited, while the matched group were set to screened patients with diabetes mellitus but no NKHC at a 1:3 ratio. The clinical and imaging data were collected for all the participants of the two groups. Firstly, Correlation analysis was conducted to test the difference of all the variables between the NKHC group and matched group. Then, the putative associated factors for NKHC were further identified. Results Eleven men and 9 women with NKHC and 60 matched participants were analyzed. The mean age of the NKHC group was 68.5 ± 14.9 years. Participants with NKHC were more likely to have a higher glycosylated hemoglobin (HbA1c) level (13 ± 2.82 vs. 10.57 ± 2.71, P<0.001), and a higher frequency of renal dysfunction (estimated glomerular filtration rates <60 ml/min/1.73m2) (55% vs. 20%, P=0.005). Logistic regression analyses showed that both higher HbA1c and renal dysfunction were significantly correlated with NKHC. Conclusion A higher value of HbA1c and renal dysfunction may be associated with the occurrence of NKHC.